2006
DOI: 10.1111/j.1398-9995.2006.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein levels in bronchoalveolar lavage after segmental allergen challenge in patients with asthma

Abstract: This study demonstrates significant alterations of all SPs in BAL fluid after allergen challenge of which SP-C was most closely related to surfactant dysfunction and the degree of the allergic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 36 publications
4
51
1
2
Order By: Relevance
“…We found no consistent association between SP-B genotypes and any of the lung diseases we examined, except for asthma. As in previous reports on SP-C [26,27], a protein related to SP-B, we did find an association between SP-B rs3024791 rare versus common homozygosity and asthma. We could not confirm this result when analysing other SP-B genotypes, and further studies will be needed to conclusively determine whether the SP-B rs3024791 AA genotype is associated with increased asthma risk.…”
Section: Discussionsupporting
confidence: 72%
“…We found no consistent association between SP-B genotypes and any of the lung diseases we examined, except for asthma. As in previous reports on SP-C [26,27], a protein related to SP-B, we did find an association between SP-B rs3024791 rare versus common homozygosity and asthma. We could not confirm this result when analysing other SP-B genotypes, and further studies will be needed to conclusively determine whether the SP-B rs3024791 AA genotype is associated with increased asthma risk.…”
Section: Discussionsupporting
confidence: 72%
“…Because SP-D function has been shown to be regulated by NO-mediated post-translational modifications, we hypothesized that acute allergic inflammation would alter SP-D structure and function. Therefore, we examined the effect of segmental challenge with antigen or endotoxin in subjects with mild allergic asthma (22)(23)(24). Here we show that acute segmental allergen challenge alone, or in combination with LPS, induces changes in SP-D multimeric structure in vivo that are associated with the loss of the ability of SP-D to inhibit eosinophil chemotaxis.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Wallaert et al [31] reported that asthmatic patients exhibited T-cell and degranulated mast cell infiltration and increased basement membrane thickness in the minor salivary glands and bronchial mucosa, suggesting that activated T cells may elicit airway-like inflammation in the salivary glands. Allergen challenge increased SP-D levels in BALF, which correlated with the degree of allergic inflammation in asthmatic lungs [32]. Animal studies in transgenic mice have shown that IL-4 and IL-13 increase SP-D expression [33].…”
Section: Salivary Sp-d Levels Correlate With R5-r20 In Asthmatic Chilmentioning
confidence: 99%